A Mixed-Methods Comparison of Self-Reported and Conversational Trust in Science - Joy N Rumble; Yu-Lun Wu; Kelsey Tully; Taylor K Ruth; Jason D Ellis Ph.D.; Alexa J Lamm (Journal of Applied Communications, 2020)
The development of science and technology highly relies on public trust in science. However, previous studies have shown that the public trust may vary across different scientific issues. This research explored how the public trust in science varied between a general and context specific environment. A convergent mixed-methods design was conducted. The results indicated participants’ self-reported general trust in in science did not change significantly between two measures. However, in conversation four major themes related to distrust were revealed. Future research is recommended to further explore how trust in science evolves in conversation and among different contexts.
Keywords: Science communication; Trust; Mixed Methods